PENGARUH PENGETAHUAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Leovika, Leovika; Trisnawati, Estralita (Jurnal Paradigma Akuntansi, 2024)
The motivation behind this study is to decide the impact of grasping data about charge evaluations, retaliation authority, and expense administration administrations on the consistency of individual citizens. The example choice involving a purposive testing technique and substantial information for 100 citizens. The information handling technique utilizes numerous relapse breaks down helped by SPSS for Windows which was conveyed 25 and Microsoft Excel 2013. The consequences of the examination demonstrate that understanding data about charge assortment and consumption sanctions influences individual citizen consistence. In the interim, the expense administration fundamentally affects individual citizen consistence.